2006
DOI: 10.1152/ajpheart.01192.2005
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine uptake inhibitors block α7-nAChR-mediated cerebral nitrergic neurogenic vasodilation

Abstract: We have proposed that activation of cerebral perivascular sympathetic alpha7-nicotinic acetylcholine receptors (alpha7-nAChRs) by nicotinic agonists releases norepinephrine, which then acts on parasympathetic nitrergic nerves, resulting in release of nitric oxide and vasodilation. Using patch-clamp electrophysiology, immunohistochemistry, and in vitro tissue bath myography, we tested this axo-axonal interaction hypothesis further by examining whether blocking norepinephrine reuptake enhanced alpha7-nAChR-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…SA, PA, and other saturated fatty acids with Ͻ20 hydrocarbon chains have been shown to potentiate ACh-induced, ␣7-nAChR-mediated inward currents, leading to facilitation of hippocampal neurotransmission (31). The postganglionic neurons/cell bodies of the rat SCG also are endowed with ␣7-nAChR (10,25,27). Whole-cell patch-clamp studies, however, demonstrated that PAME (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…SA, PA, and other saturated fatty acids with Ͻ20 hydrocarbon chains have been shown to potentiate ACh-induced, ␣7-nAChR-mediated inward currents, leading to facilitation of hippocampal neurotransmission (31). The postganglionic neurons/cell bodies of the rat SCG also are endowed with ␣7-nAChR (10,25,27). Whole-cell patch-clamp studies, however, demonstrated that PAME (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Detailed methods are found in SI Text. SCG cell culture.Detailed methods of culturing SCG neuronal cells (10,32) are found in SI Text. Electrophysiology.…”
Section: Gc/msmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-cell recording from neurons were obtained according to our previous reports (Si and Lee, 2002;Long et al, 2006; Chen et al, 2012) and those by others (Hamill et al, 1981). The recording electrodes pulled by a P-97 microelectrode puller (Sutter, Novato, CA) were filled with the intracellular solution composed of (in mM) K-gluconate 145, KCl 10, EGTA 1, and HEPES 10, at pH 7.4, and had resistance of 8-18 MΩ.…”
Section: Whole-cell Patch Clamp Technique On Dissociated Scg Neuronsmentioning
confidence: 99%
“…This is a new description of the autonomic control of the blood flow at least in the brainstem. Furthermore, nicotineinduced axo-axonal interaction-mediated dilation of isolated porcine basilar arteries is blocked by b-amyloid peptides (Si & Lee 2002, Si et al 2005, cholinesterase inhibitors (Mozayan et al 2006) and monoamine uptake inhibitors (Long et al 2006) and diminishes in hypertension (Chang et al 2012). All blockade by these different substances and inhibitors in normal animals is due to inhibition of nAChRs and is prevented by statins (Si et al 2005, Mozayan et al 2006, Mozayan & Lee 2007) and oestrogen (Si et al 2011) but not by testosterone (Lee et al 2011b).…”
mentioning
confidence: 99%